2008
DOI: 10.1029/2008ja013059
|View full text |Cite
|
Sign up to set email alerts
|

Solar‐minimum quiet time ion energization and outflow in dynamic boundary related coordinates

Abstract: [1] We report hemispheric average fluxes and energies of outflowing energetic (0.015 < E/q < 33 keV) H + , O + , and He + ions in dynamic boundary-related coordinates, from observations obtained by the Polar/TIMAS instrument near 6000 km altitude in the southern hemisphere during quiet geomagnetic intervals at solar minimum. We discuss our observations in terms of known energization and transport processes. We find that only a small fraction of energetic ions escape from the ionosphere directly into the polar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
75
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 39 publications
11
75
1
Order By: Relevance
“…Our mean outflow of 0.74×10 26 confirms this conclusion. The value is also very close to the cold ion outflow measured previously at low altitudes Cully et al, 2003a;Nagai et al, 1984) (see Table 1 of ) and the total outflow at high altitude measured as flux by Su et al (1998) and equated as total outflow by Peterson et al (2008). This has several implications: (1) The cold ion outflows from the high-latitude ionosphere extend far back in the geomagnetic tail (to at least 19 R E ).…”
Section: Comparison To Previously Published Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…Our mean outflow of 0.74×10 26 confirms this conclusion. The value is also very close to the cold ion outflow measured previously at low altitudes Cully et al, 2003a;Nagai et al, 1984) (see Table 1 of ) and the total outflow at high altitude measured as flux by Su et al (1998) and equated as total outflow by Peterson et al (2008). This has several implications: (1) The cold ion outflows from the high-latitude ionosphere extend far back in the geomagnetic tail (to at least 19 R E ).…”
Section: Comparison To Previously Published Resultssupporting
confidence: 57%
“…As was mentioned in the introductory section, there have been a large number of studies on ion outflow from the polar caps at low altitudes using different spacecraft: DE-1 (Nagai et al, 1984;Chandler et al, 1991), Akebono (Abe et al, 1993(Abe et al, , 1996(Abe et al, , 2004Cully et al, 2003a), and Polar (Moore et al, 1997;Su et al, 1998;Chappell et al, 2000;Lennartsson et al, 2004;Liemohn et al, 2005;Huddleston et al, 2005;Peterson et al, 2006Peterson et al, , 2008. The study at highest altitude so far was conducted by Su et al (1998) using Polar data at apogee altitude at 8 R E above the polar caps.…”
Section: Comparison To Previously Published Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ion data from Cluster and Polar have revealed that a large amount of ionospheric ions are kept supplied to the exterior cusp, plasma mantle and magnetosheath, with a total flux of about 10 24−26 s −1 (Peterson et al, 2008;Slapak et al, 2013Slapak et al, , 2015 and with a local number density ratio to the solar wind of about 1 %. This amount is sufficient to substantially decelerate the solar wind by about 10 % because of 16 times heavier mass of O + than H + , and might significantly influence the electrodynamics of the polar ionosphere, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Peterson et al, 2008), the mass-loading effect should also be localized and completely independent of the massloading effect of the ionospheric E region mentioned above. Therefore, this effect must be considered differently than the traditional solar wind-magnetosphere-ionosphere coupling.…”
Section: Introductionmentioning
confidence: 99%